Islamic Counseling Therapy To Improve The Happiness Of Broken Home Children In Class X Madrasah Aliyah - Fadilah, Nurul; Darmayanti, Nefi; Al Farabi, Mohammad (Yana Research, 2023)
This study aims to determine Islamic counseling therapy to increase the happiness of broken home children in class X. The research approach used is quantitative, the type of research used is guidance and counseling (PTBK). The research instrument that researchers use to obtain the results of Islamic counseling therapy to increase the happiness of broken home children in students is by distributing questionnaires to research subjects, namely class X students of Madrasah Aliyah Al-Jam'iyatul Wasliyah Medan Tembung. After getting the results of distributing the questionnaire to students, the researcher can proceed to the stage of applying the Islamic guidance and counseling model in the form of prayer therapy, and dhikr & al-Qur'an therapy to students who experience broken homes who are at a high category level which is called a group experiment. Based on the results of the researchers' findings that the school has implemented the same thing as will be researched and conducted research at the school, but this cannot run conducively and does not match the expectations of the school because of a lack of seriousness and still a lack of control from the teacher as well as from the students. Students at the Madrasah Aliyah Al-Jam'iyatul Wasliyah Tembung school follow the hours that have been set for the prayer schedule and they all follow it properly and regularly but when carrying out the Al-Qur'an reading process there are still some students who are not good at all reading the Qur'an and for dhikr they can do it smoothly and well. So it can be concluded that Islamic counseling therapy to increase the happiness of broken children can increase the happiness of broken home children in students.